2014
DOI: 10.1021/ol502013f
|View full text |Cite
|
Sign up to set email alerts
|

Urupocidin A: A New, Inducing iNOS Expression Bicyclic Guanidine Alkaloid from the Marine Sponge Monanchora pulchra

Abstract: Urupocidins A and B (1 and 2), bisguanidine alkaloids with an unprecedented skeleton system, derived from polyketide precursors and containing an unusual N-alkyl-N-hydroxyguanidine moiety, have been isolated from the sponge Monanhora pulchra. The structures of 1 and 2, including absolute configuration, were established using the detailed analysis of 1D and 2D NMR, CD, and mass spectra as well as chemical transformations. Compound 1 increases nitric oxide production in murine macrophages via inducing iNOS expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 28 publications
2
32
0
Order By: Relevance
“…Separation of the mixture and purification were carried out by repeated HPLC to provide pure urupocidin A ( 2 ) (Figure 1). The structure of the compound was assigned through comparison of its spectral data with those reported earlier [8]. The semi-synthetic derivatives ( 3 ) and ( 4 ) (Figure 1) were obtained from urupocidin A by an alkaline hydrolysis or a hydrogenation as described earlier, and structures of these compounds were assigned through comparison of their spectral data with those reported earlier at the structure elucidation of urupocidin A [8].…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Separation of the mixture and purification were carried out by repeated HPLC to provide pure urupocidin A ( 2 ) (Figure 1). The structure of the compound was assigned through comparison of its spectral data with those reported earlier [8]. The semi-synthetic derivatives ( 3 ) and ( 4 ) (Figure 1) were obtained from urupocidin A by an alkaline hydrolysis or a hydrogenation as described earlier, and structures of these compounds were assigned through comparison of their spectral data with those reported earlier at the structure elucidation of urupocidin A [8].…”
Section: Resultsmentioning
confidence: 88%
“…In recent years it has been shown that the far-eastern marine sponge Monanchora pulchra is also a rich source of novel pentacyclic [3,4,5,6,7], bicyclic [8] and acyclic guanidine alkaloids [9,10]. It is interesting that alkaloids produced in the sponges from different locations and depths had a variety of structures.…”
Section: Introductionmentioning
confidence: 99%
“…For the construction of the bicyclic ring, this fatty acid could be incorporated through a Mannich condensation between positions C-3 and C-4 starting as could also be the case for the already known and simpler cimipronidine, a monocyclic derivative found in a plant (Fabricant et al, 2005;Godecke et al, 2009). The recent discovery of uropocidin A with a third alkyl chain at C-7 would support this hypothesis as an additional Mannich condensation could occur at this position (Makarieva et al, 2014). We thus propose the following alternative for the biosynthesis of crambescins that is based on a central role of the already known guanidinated proline (Scheme 1).…”
Section: Resultsmentioning
confidence: 92%
“…Stimulation of NO production in the cells is a relatively rare phenomenon for low molecular weight marine natural products. 15 On the basis of these observations, luzonicoside A (1) seems to be promising for further investigation as a potent immunomodulatory agent.…”
Section: Journal Of Natural Productsmentioning
confidence: 99%
“…Comparison of the 1 H and 13 C NMR data of the aglycon moieties of glycosides 6 and 4 suggested that 6 has the same (20R)-23-oxo-cholestane side chain, and its aglycone differs from that of 4 only in the structure of ring B (Tables 1 and 2). The 1 H, 13 C, and DEPT NMR spectra of 6 contained signals for two angular Me groups CH [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]0.85;δ C 12.7,13.5), one methine group CH-3 (δ H 3.77, δ C 78.8) associated with oxygen, an α,β-unsaturated ketone [C-6 (δ C 202.4)], and a 7(8) double bond (δ H 5.65 (t, J = 2.2 Hz); δ C 123. 5, 166.7), encountered earlier in two steroids from starfish, i.e., asterasterols B and C. 14 The COSY, HSQC, ROESY, and HMBC cross-peaks supported the 3β-hydroxy-5α-cholest-7-en-6,23-dione as the aglycon moiety in 6 ( Figure 1C).…”
Section: Journal Of Natural Productsmentioning
confidence: 99%